The Impact of Brand Image on Customer Loyalty in Private Universities: Dampak Brand Image terhadap Loyalitas Pelanggan pada Perguruan Tinggi Swasta (Jurnal Ilmu Manajemen dan Bisnis, 2023)
The existence of customer loyalty for the company is very important. Customer loyalty is defined as people who enjoy services, especially those who receive services regularly and repeatedly. This definition places loyalty as a commitment to an attitude that generates empathy. In this research about the impact of brand image and consumer satisfaction on customer loyalty. The population in this study are customers of private universities in Gorontalo. The number of samples used is 96 respondents, the sampling technique is using purposive sampling. The data obtained and analyzed qualitatively obtained through observation and data collection. The results showed that brand image has a significant influence on customer satisfaction, which is significant for customer loyalty.
Keywords: Loyalty, Customers, Private Universities, Brand Image.